Они сражались за Родину - Шолохов Михаил Александрович; Шолохов Михаил Александрович (1980)
Экземпляры: ЦБ (2002) / Инвентарный номер: 35411 / Цена: 10.00 / Авт.знак: Ш 78Т. 7 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6